2020
DOI: 10.1038/s41598-020-60158-4
|View full text |Cite
|
Sign up to set email alerts
|

Human primary endothelial label-free biochip assay reveals unpredicted functions of plasma serine proteases

Abstract: Tissue-on-a-chip technologies are more and more important in the investigation of cellular function and in the development of novel drugs by allowing the direct screening of substances on human cells. Constituting the inner lining of vessel walls, endothelial cells are the key players in various physiological processes, moreover, they are the first to be exposed to most drugs currently used. However, to date, there is still no appropriate technology for the label-free, real-time and high-throughput monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The group used the same principle to investigate the role of plasma proteases on endothelial cell layers. [ 147 ] The resonant wavelength shifts in response to the refractive index changes in the evanescent field and are proportional to the optical density above the surface, representing information about the cell–substrate interactions or the presence of biomolecules. [ 148 ]…”
Section: Advanced Sensing Systems and Devices For Monitoring Of Cell ...mentioning
confidence: 99%
“…The group used the same principle to investigate the role of plasma proteases on endothelial cell layers. [ 147 ] The resonant wavelength shifts in response to the refractive index changes in the evanescent field and are proportional to the optical density above the surface, representing information about the cell–substrate interactions or the presence of biomolecules. [ 148 ]…”
Section: Advanced Sensing Systems and Devices For Monitoring Of Cell ...mentioning
confidence: 99%
“…Using a human umbilical vein EC (HUVEC) model, we showed that MASP-2 is also a potent permeability-increasing enzyme. Although both the mechanism and the kinetics are very similar to those of thrombin and MASP-1 [ 98 ], the involvement of PARs in its activity is yet to be proven. We found a significant increase in MASP-2 levels in the 1/3 of patients during angioedema attacks [ 99 ], which supports the notion that MASP-2 may contribute to edema formation.…”
Section: Permeability Modifying Mediatorsmentioning
confidence: 99%
“…Increased leukocyte trafficking and enhanced ICAM-1 and VCAM-1 expression was demonstrated in the presence of PKa [ 101 ], which may modulate permeability indirectly through pro-inflammatory cytokines. PKa can cleave endothelial VE-cadherin in AJs [ 102 ]; moreover, as we have shown, it can activate ECs (possibly via PAR cleavage) and thereby directly increases endothelial permeability [ 98 ].…”
Section: Permeability Modifying Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few decades, label-free optical biosensors have proven their unique capabilities in a wide range of applications from biomolecular interaction analysis (BIA) [1][2][3][4] to whole-cell monitoring [5][6][7][8][9] . Screening the interactions of various analyte-ligand pairs has become essential in drug discovery [10][11][12][13] , assay and sensor development 14,15 as well as for understanding molecular mechanisms in biochemistry and biophysics [16][17][18][19] . Often, the introduction of labels is simply impossible in such measurements, and the application of label-free methods is the only reliable choice.…”
mentioning
confidence: 99%